Has trade with China affected UK inflation? - Tracy Wheeler (Bank of England, External Monetary Policy Committee Unit, 2008)
This paper investigates empirically whether the level or growth of cheap imports from China has had an impact on UK inflation. We use two methods; the first calculates UK weighted world export price inflation as the sum of the effect of the inflation level in the UK's trading partners and the effect of substituting imports from more expensive countries with imports from countries with lower price levels. The second estimates these two effects on UK inflation using panel regressions. The results from the first method suggest that the substitution of imports from more expensive countries with imports from China reduced UK weighted world export price inflation by an average of -0.75 percentage points per annum from 2000 to 2004. Similarly, the panel regressions suggest that over the 1997-2005 period this substitution had a small but significant downward impact on UK CPI inflation. However, the same regressions also suggest that higher inflation in imports from China than in imports from other countries has put upward pressure on some components of UK CPI inflation. As this upward 'inflation effect' is likely to have outweighed the downward 'substitution effect' the regressions suggest that the overall effect of Chinese imports on UK CPI inflation from 1997-2005 was positive.
Keywords: E31; F15; 330; Inflation; China; Imports; Import; Chinesisch; Lebenshaltungsindex; Großbritannien